Learning interaction in the digital era: Technological innovations and education management strategies to enhance student engagement - Adiyono, Adiyono; Hayat, Eka Wardatul; Oktavia, Elsa Dewi; Prasetiyo, Nova Tri (Univeritas Papua, 2024)
In the digital age, the use of technology in the learning process has a significant impact on student engagement. This research analyzes learning interactions in the digital era with a focus on the effects of technological innovation and educational management strategies on student engagement. This study used a mixed methods research design consisting of quantitative and qualitative data collection techniques. A sample of 30 students at MAN Paser was selected using a stratified random sampling technique. The students were asked to complete a self-administered questionnaire measuring their level of engagement using a five-point Likert scale. The questionnaire consisted of 15 questions covering various aspects of student engagement, such as cognitive, behavioral, and emotional engagement. The research questions involved the influence of technology on student engagement, administrative challenges in implementing educational technology, the role of management strategies in improving digital student engagement, differences in student engagement between institutions with and without innovative technology, and other factors that influence student engagement. This research aims to provide in-depth insights into how to improve learning in the digital age through the integration of technology and effective educational management. The results and discussion of this study are expected to provide valuable contributions to educators, policymakers, and other stakeholders in designing and implementing effective digital learning strategies that enhance student engagement.